1996
DOI: 10.1089/clm.1996.14.67
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessments of the Erbium:YAG Laser for Soft Tissue Surgery and Scaling

Abstract: We evaluated the clinical usefulness of an erbium:YAG laser for soft tissue surgery, and scaling. Thirty-one patients with soft tissue lesions (13 males and 18 females from 24 to 71 years old), and 60 patients with calculus deposits (21 males and 39 females from 19 to 72 years old) were treated with the laser. The clinical parameters evaluated were pain, redness, swelling of the gingiva, and the subjective patient comfort parameters including uneasiness with the sound and vibration associated with laser treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 24 publications
3
74
0
6
Order By: Relevance
“…Carbon dioxide lasers (10.6 mm), targeting the mineral component of bone have shown some success in bone removal, but severe tissue charring can occur [11,12]. ER:YAG (2.94 mm), which has a strong water absorption, has been gaining popularity over the past few years for possible use in orthopedics, dental and maxillofacial surgery [3,13], as well as periodontal surgery applications [14]. Nonetheless, charring has still been observed with this type of laser [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide lasers (10.6 mm), targeting the mineral component of bone have shown some success in bone removal, but severe tissue charring can occur [11,12]. ER:YAG (2.94 mm), which has a strong water absorption, has been gaining popularity over the past few years for possible use in orthopedics, dental and maxillofacial surgery [3,13], as well as periodontal surgery applications [14]. Nonetheless, charring has still been observed with this type of laser [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…The favorable results of in vitro studies have led researchers to expect promising results from its clinical application. Following the first report by Watanabe et al (13), which showed the safety and usefulness of Er:YAG laser therapy for subgingival calculus removal in nonsurgical pocket therapy, several randomized, controlled clinical studies reported the effectiveness of Er:YAG laser irradiation in comparison to conventional methods using hand curets or ultrasonic scalers. In contrast however, Schwarz et al{23) reported that similar or better results were obtained following conventional scaling and root planing therapy in terms of reduction of bleeding on probing, pocket depth and improvement of clinical attachment levels, and that these clinical improvements could be maintained over a 2-year period {24).…”
Section: Non-surgical Therapymentioning
confidence: 99%
“…The CO 2 laser is not suitable since it has the potential to cause thermal damage as indicated by previous studies (11). The Er:YAG laser may hold the most promise for root surface debridement such as selective calculus removal and decontamination with bactericidal effects against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans although there is no consensus till date regarding the level of detection and calculus removal (12,13). Current laser-assisted methods address the biofilm of the tissue wall, supplementing conventional methods that address the tooth structure (14).…”
Section: I) Non-surgical Periodontal Therapymentioning
confidence: 99%